2019
DOI: 10.1038/s41467-019-13196-0
|View full text |Cite
|
Sign up to set email alerts
|

On-target restoration of a split T cell-engaging antibody for precision immunotherapy

Abstract: T cell-engaging immunotherapies are changing the landscape of current cancer care. However, suitable target antigens are scarce, restricting these strategies to very few tumor types. Here, we report on a T cell-engaging antibody derivative that comes in two complementary halves and addresses antigen combinations instead of single molecules. Each half, now coined hemibody, contains an antigen-specific single-chain variable fragment (scFv) fused to either the variable light (VL) or variable heavy (VH) chain doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Each half contains a TAA binding scFv fused to either the variable light (VL) or variable heavy (VH) chain domain of an anti-CD3 antibody. When the two complementary halves simultaneously bind their respective antigens on the same cell, they reconstitute the original CD3-binding site to engage T cells (Banaszek et al 2019 ).…”
Section: Increased Tumor Selectivitymentioning
confidence: 99%
“…Each half contains a TAA binding scFv fused to either the variable light (VL) or variable heavy (VH) chain domain of an anti-CD3 antibody. When the two complementary halves simultaneously bind their respective antigens on the same cell, they reconstitute the original CD3-binding site to engage T cells (Banaszek et al 2019 ).…”
Section: Increased Tumor Selectivitymentioning
confidence: 99%
“…Furthermore, Banaszek et al reported on hemibodies consisting of two different antigen-specific scFvs fused to the variable light or variable heavy chain domains of a CD3 antibody. If both hemibodies simultaneously bind their respective antigens on a single cell, a T-cell engaging CD3 binding domain is generated [ 97 ]. In preclinical models, hemibodies can preferentially induce the cellular lysis of double-positive cells and spare single-positive cells [ 97 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Hallmarks of tumor immune evasion, such as heterogenous expression and down-regulation of antigen levels, present obstacles to both T cell and NK cell redirecting BsAbs (79). New constructs, such as multivalent and tri-specific BsAbs, are under investigation as possible responses to these concerns (81)(82)(83). These new designs may also be pivotal in reducing toxicity.…”
Section: Bispecific Antibodies: Overview Designs and Potential For MMmentioning
confidence: 99%
“…Emerging BsAb technologies may prevent against unnecessary B and plasma cell depletion by increasing their specificity. A promising example of such technology is the "split" trispecific antibody, which is divided into two scFv halves, both connected to the same anti-CD3 antibody (83). The CD3-binding site only becomes functional when both scFvs have attached to their target antigen, ensuring that effector cell lysis is only directed at cells expressing both antigens.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation